Effect of torsional stiffness on biomechanical variables of the lower extremity during running. (2nd January 2017) - Graf, Eveline; Wannop, John William; Schlarb, Heiko; Stefanyshyn, Darren
Abstract : Torsion, the relative in-/eversion between forefoot and rearfoot, is a concept that has been incorporated into running shoes for almost 30 years. Studies have shown an influence of footwear torsional stiffness on lower extremity biomechanics during running but results are inconclusive. However, the influence of the torsion axis of the shoe on kinematics and kinetics of running has not been examined. Therefore, the goal was to examine the effect of shoes with a specially designed torsion element on running biomechanics of the lower extremities. Twenty runners performed heel–toe running at 4.0 ms −1 with three shoes and barefoot. All shoes had a torsion element based on a rearfoot and a forefoot element connected by bushings that had a defined rotation axis. The torsional stiffness was altered by modifications made to the torsion element and the surrounding midsole. A force plate and camera system were used to collect kinetics and kinematics. Foot torsion, ankle eversion, ankle and knee moments in the frontal and transverse plane and ground reaction forces were compared between conditions using paired t -tests. The shoe with the lowest torsional stiffness did not result in larger torsion range of motion compared to a stiffer shoe. Ankle eversion decreased with decreasing torsional stiffness while the changes in ankle kinetics were not consistent between the frontal and transverse plane. Torsional stiffness did not have a systematic influence on knee joint kinetics. While shoe torsional stiffness influences foot kinematics significantly, it does not affect lower extremity running biomechanics in a way that would alter the risk of running injuries.